'Googling' anaphylaxis. Issue 5 (October 2019) - Kornafeld, Anna; Gonzalez-Estrada, Alexei; Dimov, Ves
Abstract : Purpose of review: Anaphylaxis is a systemic allergic reaction and without the appropriate treatment can progress fast and may be fatal. Information about allergy and immunology topics including anaphylaxis can be easily found online and are widely searched by patients as well as medical personnel. Social media and search engines not only bring a number of benefits to users but also carry risks for breaches of confidentiality and privacy, unprofessional behaviour, malpractice and litigation. Social media use by medical healthcare workers has liability risks and can result in malpractice. Recent findings: We used PubMed with the terms anaphylaxis; social network; mobile apps that revealed a very small number of publications addressing the use of these platforms and anaphylaxis. Google Trends and KWFinder were used to analyse the relative search interest and absolute search volumes on 'anaphylaxis'. Summary: Multiple sources exist on the Internet for health-related searches for both healthcare providers and patients. We analysed different websites, mobile apps, Facebook, YouTube and Twitter. To avoid any posting of patient identifiers, it is imperative to be aware of the 18 HIPAA identifiers. We list websites with accurate information about anaphylaxis for the use of both patients and healthcare professionals for purposes of patient education. Further research on health information-seeking behaviour is clearly needed.